Brief History of the Chamorros and Filipinos in Guam - Patacsil, Peter E. (Silliman Journal, 2022)
The indigenous Chamorros of Guam and the rest of the Marianas were seafaring people who migrated from Southeast Asia to the Pacific. Guam was a Spanish colony from 1565 to 1898 when it was ceded to the United States after the Spanish-American War. When Father San Vitores established a Jesuit mission in Guam in 1668, the Chamorros numbered between 24,000 and 30,000 throughout the Marianas with approximately12,000 living in Guam. At the end of the Spanish era in 1898, there were approximately 9,800 people living in Guam including 8,600 to 8,700 Chamorros. According to the 2000 census, Chamorros comprised 37% of the island's population of 155,000. Chamorro customs still pervade the everyday life of the island. The Chamorros have absorbed immigrants into a neo-Chamorro society but still perpetuate Chamorro consciousness at the grass roots level. The Filipinos, on the other hand, have been the primary immigrants to Guam since 1638 when shipwrecked sailors from the Spanish galleon Concepcion married Chamorros and raised families. Since that time, Filipino soldiers, political exiles, construction workers, laborers, doctors, nurses, teachers, and others have migrated to the island and have made Guam their home. According to the 2000 census, Filipinos comprised 26.3% of Guam's population. The continuous immigration from the Philippines has perpetuated the heterogeneity of the "Filipino community."